A multidimensional approach to factors influencing playing level and position in a school-based soccer programme. Issue 3 (3rd July 2018) - Lovell, T. W. J.; Bocking, C. J.; Fransen, J.; Coutts, A. J.
ABSTRACT: Objectives : To examine the factors influencing selection into playing levels and playing positions in a school-based soccer programme. Methods : Anthropometry, maturation, physical capacity, technical ability and motor competence were assessed in 216 soccer players (aged 10–16 years) who participated in a school-based soccer programme. Team coaches selected players into playing levels, playing positions and provided subjective ratings of player ability. Results : Multivariate analyses of covariance showed significant large and moderate differences between playing levels ( F = 5.336, P < 0.001, η 2 = .30) and playing positions ( F = 1.974, P = 0.002, η 2 = .14) respectively, for a combination of maturation, anthropometry, physical capacity, technical ability and motor competence, when adjusted for chronological age. Discriminant analysis revealed 64.8% of cases could be correctly classified into playing level with a combination of sprint speed, agility, aerobic fitness, technical ability and motor competence. Large differences in subjective coach ratings were found between positions for players in the highest playing level ( F = 2.598, P = 0.001, η 2 = .16). Conclusions : These findings contribute new evidence to highlight how individual characteristics influence the selection process in recreational youth soccer, which have important implications for talent development pathways in schools, clubs and academies.